Reinforcement of Interfacial Adhesion of a Coated Polymer Layer on a Cobalt-Chromium Surface for Drug-Eluting Stents - Bedair, Tarek M.; Cho, Youngjin; Kim, Tae Jung; Kim, Young Dong; Park, Bang Ju; Joung, Yoon Ki; Han, Dong Keun (AMER CHEMICAL SOC, 2014)
During the balloon expansion of several commercially available drug-eluting stents, various types of defects in the polymer layer have been observed. The aim of this study is to prevent these defects by increasing the interfacial adhesion between the metal substrate and the drug-in-polymer matrix using poly(caprolactone) (PCL) brushes onto a cobalt-chromium (Co-Cr or CC) alloy surface. The chemical modification of the Co-Cr surface was accomplished by grafting ricinoleic acid (RA) onto the metal substrate followed by surface-initiated ring opening polymerization of epsilon-caprolactone. The unmodified, RA-grafted (CC-RA), and PCL-grafted Co-Cr substrates (CC-RA-PCL3D and CC-RA-PCL6D) were characterized by various surface analyses. Poly(D,L-lactide) containing sirolimus was spray coated onto the unmodified and modified substrates. The adhesion property of the polymer coating on the PCL-grafted surfaces was improved compared to those of other samples. Among all of the drug-in-polymer coated samples, both CC-RA-PCL3D and CC-RA-PCL6D exhibited a stabilized drug release profile over 49 days. It was also revealed that CC-RA-PCL6D showed the slowest drug release of all the samples. On the basis of these results, the proposed nanocoupling method has shown not only improved adhesion of the drug-in-polymer matrix to the Co-Cr substrate but also controlled drug release.
Keywords: SELF-ASSEMBLED MONOLAYERS; RING-OPENING POLYMERIZATION; CORONARY-ARTERY-DISEASE; NEOINTIMAL HYPERPLASIA; ALLOY; OXIDE; SIROLIMUS; RELEASE; NANOPARTICLES; DEPOSITION